Readiness and challenges of post-endemic COVID-19 e-learning implementation among university students: a preliminary study / Hazwani Abdul Wahab and Siti Nur Izyandiyana Ab Hadi - Abdul Wahab, Hazwani; Ab Hadi, Siti Nur Izyandiyana (Faculty of Communication & Media Studies, 2023)
The employment of e-learning or online instruction has persisted beyond the post-COVID-19 era. In fact, several sophisticated and state-of-the-art tools have been developed to streamline the online learning experience for students. All groups of students, regardless of primary school level to higher education level, have started to adapt to e-learning in their learning process. Therefore, the researcher seeks to investigate whether students, particularly at the tertiary level, possess the necessary readiness to effectively execute e-learning. The objective of this study is to identify the level of readiness of Sultan Azlan Shah University students in using e-learning and to identify the challenges faced by students in implementing e-learning. The study was conducted on 38 undergraduate students from the Islamic Studies Bachelor's Degree program at Sultan Azlan Shah University. The study found that students are still not fully ready to implement e-learning and lack encouragement from parents to participate in e-learning while at home with the highest score being.